Determination of lipophilic and hydrophilic antioxidant activities in the crude extracts of ten varieties of tomatoes - Sricharoen, Phitchan; Techawongstein, Suchila; Chanthai, Saksit (Asia-Pacific Journal of Science and Technology, 2015)
In this study, both lipophilic and hydrophilic antioxidant activities in ten varieties of tomato (Lycopersicon esculentum Mill.) crude extracts were determined using three common assays, namely 2,2-diphenyl-1-picryl-hydrazyl (DPPH), 2,2'-azinobis(3-ethylebenzothiaziline-6-sulfonate) (ABTS) and ferric reducing antioxidant power (FRAP). All the tomato samples exhibited the same activity as that of Trolox. The highest total antioxidant activity (both lipophilic and hydrophilic antioxidant) was found in Black Cherry Kham Kaen while that of Mo Kho 40 sample was the lowest. The average values in terms of TEAC were 910.2, 989.4 and 1174 as determined by ABTS, DPPH and FRAP, respectively. These results demonstrated the potential role of high antioxidant property found in all tomato samples